786 Retrospective analysis of paediatric ENT surgery outcomes during the COVID pandemic. (4th May 2021) - Huang, J; Bhargava, E; Walsh, M; Pennell, D; Attya, H; Jablenska, L; Ferguson, L; Lilly, I; Pepper, C; Tweedie, D; Possamai, V
Abstract: Introduction: Studies show high morbidity/mortality for adults with peri-operative SARS-CoV-2 infection, leading to recommendations curtailing elective operations during the height of the pandemic. Our understanding of the risks associated with paediatric surgery is more limited, with preliminary data suggesting lower morbidity/mortality than in adults. A < 1% incidence of COVID-19 in paediatric patients undergoing preoperative universal screening is reported, and even in those testing positive, morbidity and mortality seem to be low. As waiting lists swell and the detriment associated with delaying surgery mounts, it is imperative to accurately quantify the risks of surgery in the paediatric population. Method: Retrospective review of all paediatric ENT operations performed at the Evelina Children's Hospital at the height of lockdown, from March to May 2020. Results: 61 procedures were performed on 56 patients. 50% had a pre-operative SARS-CoV-2 nasopharyngeal swabs. All cases involved a change in anesthetic practice; 2 cases involved a change in surgical practice. We noted 2 medical complications and 1 surgical complication. All patients are currently extant. No staff or patients subsequently developed COVID. Conclusions: Our perioperative infection rates and mortality/morbidity figures concord with figures published elsewhere in literature. We are cautiously optimistic regarding risks associated with paediatric ENT surgery.